Geochemistry of Lake Tinninilik, Greenland, July 2022 ... - Diaz, Melisa; Gardner, Christopher (NSF Arctic Data Center, 2024)
Lake Tinninilik is an ice-marginal lake in western Greenland. It is dammed by Sarqardliup Glacier to the East and North, and drains on a quasi-decadal timescale when lake volume reaches a critical threshold. When Lake Tininnilik does drain, it discharges ~2 cubic kilometers (km3) of lake water in Sarqardleq Fjord to the North. Samples were collected in July 2022 from streams around the lake and surface and depth water samples from the lake itself. The lake samples were collected using a niskin onboard an inflatable dinghy. Trace metal (ICP-MS), ion (ion chromatography), and nutrient (colorimetric nutrient analysis) geochemical data were generated from the Lake Tinninilik samples to understand whether the Greenland ice-marginal lakes are an important source of nutrients to coastal waters into which they drain. ...